Penindakan Propam (Profesi dan Pengamanan) Terhadap Anggota Polisi Lalu Lintas Yang Melampai Kewenangannya Dalam Menjalankan Tugas (Studi di Kepolisian Resort Kota Besar Medan) - Khairul Nizam (Universitas Islam Sumatera Utara, 2020)
Members of the traffic police must be firm in taking action against traffic violations, but must not deviate from the duties they carry.The deviation of behavior of the members of the Police of the Republic of Indonesia above is a violation of the discipline rules of the members of the Police of the Republic of Indonesia as regulated in Government Regulation of the Republic of Indonesia Number 2 of 2003 concerning Discipline Regulations of the members of the Police of the Republic of Indonesia.The formulation of the problem in this thesis research is what are the factors causing the abuse of authority carried out by the traffic police at Medan City Police Resort, how is the action taken by Propam(Profession and Security) against traffic police that exceeds their authority in carrying out their duties at Medan City Police Resort, and how to deal with against traffic police who exceeded their authority in carrying out their duties at Medan City Police Resort.The research method used is descriptive analysis that leads to empirical juridical legal research that is research conducted by examining primary data by obtaining them directly from sources or interviews and secondary data by processing data from primary legal materials, secondary legal materials and tertiary legal materials.The result showed that the factors causing the abuse of authority by the traffic police in Medan City Police Resort were economic factors, namely the lack of income earned by a police officer that was not comparable with the high cost of leaving. The action taken byPropam(Profession andSecurity) against traffic police who exceeded their authority in carrying out their duties in Medan City Police Resort was to impose sanctions for disciplinary violations against members of the Indonesian Police. The handling of traffic that exceeds their authority in carrying out their duties in Medan City Police Resort, among others, by holding a discussion of cases so that a commitment is made to the decision to be taken as a member of the traffic police with restrictions so as not to occur abuse of authority, carried out for justice and the public interest. Key-Words: Repression, Profession and Security (Propam), Beyond Authority.